Pocket Oxford Dictionary, Thesaurus, and Wordpower Guide - Edited by Hawker, Sara (Oxford, New York Oxford University Press, 2004)
Authoritative, compact, and up to date, this three-in-one reference contains a dictionary with over 90,000 words, phrases, and definitions; a thesaurus with over 130,000 alternative words; and a Wordpower Guide to help improve your vocabulary skills.
Keywords: English language -- English language--Synonyms and antonyms